ANALYSIS OF LIBRARY SERVICES AND INTERESTING LIBRARY DESIGN IN INCREASING INTEREST IN VISITING STUDENTS OF MAN 1 MEDAN - hasibuan, Aisyah Fadilah; Evy Juliani Siregar; Fatimah Azzahra Lubis; Maisa Muti Salsabila Hasibuan; Zaidan Kholis (Journal of Educational Science Learning and Research, 2025)
This study aims to analyze the effect of library design and service quality on student interest in visiting the MAN 1 Medan library. The method used is qualitative research method used to create a comprehensive and complex picture of library services and library design at MAN 1 MEDAN. The results showed that attractive library design has a significant positive influence on student visitation interest. Modern and ergonomic design, the use of bright colors, and layouts that facilitate accessibility are important factors that increase student comfort while in the library. Meanwhile, high service quality also has a significant effect on visitation interest. Friendly service, fast lending process, and the availability of competent staff are key in increasing user satisfaction.